EDUKASI MENGENAI EPILEPSI PADA PENGUNJUNG POLI NEUROLOGI DI RS UNIVERSITAS MATARAM - I Kadek Dwi Semadi; Setyawati Asih Putri; Baiq Hilya Kholida; Stephanie Elizabeth Gunawan; Safat Wahyudi; Anissa Diyanabila Indrasari; Baiq Ghassani Kayla; Fiana Damayanti; M. Andre Darmawan; Nasywa Aulia Safitri; Ulul Azmi (Jurnal Abdi Insani, 2026)
Epilepsy is a neurological disorder characterized by a tendency for recurrent seizures, which can lead to neurobiological, cognitive, psychological, and social consequences. Globally, epilepsy is one of the most common neurological disorders and can result in significant morbidity and mortality. Education about epilepsy plays a crucial role in improving public understanding of the condition, including recognizing seizure triggers and knowing the appropriate initial steps to take during a seizure. This activity aimed to evaluate the effectiveness of epilepsy education among visitors to the neurology clinic at the University of Mataram Hospital. The educational session was conducted through a presentation using visual aids and a question-and-answer segment. The effectiveness was assessed by comparing participants’ pre-test and post-test scores, which measured their level of understanding. The results showed that the average post-test score increased to 95.29, compared to a pre-test average of 82.35. This demonstrates that the educational activity successfully improved participants’ knowledge about epilepsy. The counseling method proved effective in enhancing the understanding of neurology clinic visitors regarding epilepsy. To broaden the impact of this educational effort, wider dissemination of information across various hospitals is needed to raise public awareness and understanding of epilepsy.